PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL, SISTEM PENGENDALIAN INTERN DAN KUALITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (STUDI KASUS INSPEKTORAT KABUPATEN BENGKULU TENGAH) - Novita Fitriyani; Helmi Herawati (Jurnal Ilmu Akuntansi, 2019)
This study aims to determine how much influence the Accrual Based Accounting, Internal Control Systems and Financial Statement Quality on the Accountability of Government Institution Performance, at the Central Bengkulu District Inspectorate.Based on the results and hypothesis testing that has been described, accrual-based accounting has a significant effect with the value of 0.714 on the accountability of government performance in the Central Bengkulu District Inspectorate. This shows that in the first hypothesis Accrual Based Accounting the hypothesis is accepted. The internal control system has a significant effect with a value of 0.801 on the accountability of government performance in the Central Bengkulu District Inspectorate. This shows that in the second hypothesis, the internal control system is accepted. The quality of financial statements has a significant effect with a value of 0.774 on the accountability of government performance in the Central Bengkulu Inspectorate, this shows in the third hypothesis The quality of the financial statements is accepted. So that it can be concluded that Accrual Based Accounting, Internal Control System and Quality of Financial Statements have a significant effect on the accountability of the performance of government agencies in the Central Bengkulu Inspectorate, with a value of 82% and the rest is influenced by other factors outside the X variable in this study.